2020
DOI: 10.1016/j.breast.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pathologic stages on postmastectomy radiation therapy in breast cancer receiving neoadjuvant chemotherapy and total mastectomy: A Cancer Database Analysis

Abstract: Purpose To use pathologic indicators to determine which patients benefit from postmastectomy radiation therapy (PMRT) for breast cancer after neoadjuvant chemotherapy (NACT) and total mastectomy (TM). Patients and methods We enrolled 4236 patients with breast invasive ductal carcinoma who received NACT followed by TM. Cox regression analysis was used to calculate hazard ratios (HRs) and confidence intervals; independent predictors were controlled for or stratified in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 45 publications
10
37
0
Order By: Relevance
“…According to previous studies, pathologic responses and pathologic stages after neoadjuvant treatments are significant prognostic factors for OS, especially pCR. 2,54,55 Therefore, the survival rate in our NACT group, with its more favorable pathologic responses and earlier pathologic stages, was superior to that of the NET group; this finding is also compatible with reported findings. 54,55 The novelty of our study is its investigation of whether NET is an alternative neoadjuvant treatment for NACT in strongly HR-positive and ERBB2-negative breast IDC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to previous studies, pathologic responses and pathologic stages after neoadjuvant treatments are significant prognostic factors for OS, especially pCR. 2,54,55 Therefore, the survival rate in our NACT group, with its more favorable pathologic responses and earlier pathologic stages, was superior to that of the NET group; this finding is also compatible with reported findings. 54,55 The novelty of our study is its investigation of whether NET is an alternative neoadjuvant treatment for NACT in strongly HR-positive and ERBB2-negative breast IDC.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is compatible with previous findings. 54 , 55 No evidence had previously indicated that menopausal status is a prognostic factor of OS in strongly HR-positive and ERBB2 -negative breast IDC. To our knowledge, the current study is the leading study to demonstrate that premenopausal status is an independent poor prognostic factor in OS of strongly HR-positive and ERBB2 -negative IDC ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, adjuvant WBRT was a signi cant prognostic factor for OS, LRR, and DM compared with no adjuvant WBRT in women with left-side IDC and HFrEF receiving BCS; moreover, old age (>65 years), CCI ≥ 1, advanced pT stages (pT2-4), advanced pN stages (pN1-3), hormone receptor negative status, and differentiation Grade II-III were signi cant prognostic factors for OS, compatible with ndings of previous studies. [10,11,[42][43][44][45][46][47][48][49] Moreover, advanced pN stages (pN1-3), hormone receptor negative status, and differentiation Grade II-III were signi cant poor prognostic factors for LRR and DM in women with left-side breast IDC and HFrEF receiving BCS, which is also compatible with ndings of previous studies. [10,11,[42][43][44][45][46][47][48][49] Our ndings of prognostic factors for OS, LRR, and DM in women with IDC and HFrEF receiving BCS are similar with those of previous studies, [10,11,[42][43][44][45][46][47][48][49] and no additional prognostic factor has been identi ed in previous studies other than the ones determined in the current study irrespective of whether underlying HFrEF was present.…”
Section: Discussionsupporting
confidence: 83%
“…[10,11,[42][43][44][45][46][47][48][49] Moreover, advanced pN stages (pN1-3), hormone receptor negative status, and differentiation Grade II-III were signi cant poor prognostic factors for LRR and DM in women with left-side breast IDC and HFrEF receiving BCS, which is also compatible with ndings of previous studies. [10,11,[42][43][44][45][46][47][48][49] Our ndings of prognostic factors for OS, LRR, and DM in women with IDC and HFrEF receiving BCS are similar with those of previous studies, [10,11,[42][43][44][45][46][47][48][49] and no additional prognostic factor has been identi ed in previous studies other than the ones determined in the current study irrespective of whether underlying HFrEF was present.…”
Section: Discussionsupporting
confidence: 83%
“… 17 The TCRD of the Collaboration Center of Health Information Application contains detailed patient information, such as clinical stage, pathological stage, surgical margin status, surgical procedures, treatment techniques, radiotherapy, chemotherapy regimens, and follow-up visits. 5 , 6 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Our protocols were reviewed and approved by the institutional review board of Tzu-Chi Medical Foundation. Patient consent was waived because data files are deidentified by scrambling the identification codes of both patients and medical facilities and sent to the National Health Research Institutes to form the original files of NHIRD.…”
Section: Methodsmentioning
confidence: 99%